2017
DOI: 10.11606/issn.2316-9079.v16i2p155-182
|View full text |Cite
|
Sign up to set email alerts
|

Redescrição dos girinos de Epipedobates narinensis e E. boulengeri (Anura: Dendrobatidae).

Abstract: Redescription of the tadpoles of Epipedobates narinensis and E. boulengeri (Anura: Dendrobatidae). The larval morphology of poison frogs (Dendrobatoidea) has contributed to an understanding of the phylogenetic relationships within the superfamily. Nevertheless, our knowledge of larval morphology is incomplete. The larvae of the dendrobatids, and are redescribed, diagnosed, and differentiated from three congeners, as well as sympatric dendrobatoids and closely related genera. Three larval developmental phases a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 12 publications
0
4
0
Order By: Relevance
“…It would be interesting to collect tadpoles of the new species for comparison with other Epipedobates species. Comparisons of larval stages made by Anganoy-Criollo and Cepeda-Quilindo (2017) detected some differences between the populations of Ecuador and southwest of Colombia in body shape, tips of marginal papillae, and pattern of tail coloration. However, the specimens from Colombia used in their study likely correspond to E. boulengeri -Nariño ( E. boulengeri sensu stricto ) and we are not certain of the identification of the specimens from Ecuador, which could correspond to E. aff.…”
Section: Resultsmentioning
confidence: 96%
See 2 more Smart Citations
“…It would be interesting to collect tadpoles of the new species for comparison with other Epipedobates species. Comparisons of larval stages made by Anganoy-Criollo and Cepeda-Quilindo (2017) detected some differences between the populations of Ecuador and southwest of Colombia in body shape, tips of marginal papillae, and pattern of tail coloration. However, the specimens from Colombia used in their study likely correspond to E. boulengeri -Nariño ( E. boulengeri sensu stricto ) and we are not certain of the identification of the specimens from Ecuador, which could correspond to E. aff.…”
Section: Resultsmentioning
confidence: 96%
“…Unfortunately, we did not collect larval stages of E. [to be revealed] . Larval morphology of Dendrobatoidea has contributed to understanding of the phylogenetic relationships within the superfamily (Anganoy-Criollo & Cepeda-Quilindo, 2017). It would be interesting to collect tadpoles of the new species for comparison with other Epipedobates species.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Anganoy-Criollo and Cepeda-Quilindo (2017) found that tadpoles of E. boulengeri from southern Colombia (Maragrícola and Tumaco, Nariño) were phenotypically distinct from tadpoles of E. “ boulengeri ” from northwestern Ecuador. However, their Ecuadorian populations include several populations that we consider belong to E. aff.…”
Section: Discussionmentioning
confidence: 92%